Ethical practice in participant-centred linguistic research - Atkins Sarah; Mackenzie Jai; Jones Lucy (Linguistics)
This article outlines ethical principles for ‘participant-centred linguistic research’ (PCLR), a term we coin to incorporate a range of linguistic research approaches that place importance on the involvement of participants. Linguistics, as a field, has strengthened its focus on participant-centred and socially situated research, recognising the value of better understanding our participants’ practices and linguistic knowledge. However, this also brings ethical challenges for our research practice. Drawing on three differing UK-based case studies from the authors’ own work, the article explores complex issues that can arise during PCLR and establishes four key principles that cut across our varied experiences. Firstly, we address participant consent and confidentiality, establishing the principles: 1. Informed consent and ethics protocols are dialogic processes and 2. Expectations around confidentiality and anonymity can shift during a project. Secondly, we address our research relationships with participants, our key principles being: 3. The researcher-participant relationship is complex and variable and 4. Close attention must be paid to power dynamics within the research setting. Ultimately, we argue that the human interactions and relationships involved in PCLR mean research may inevitably be somewhat unpredictable; researchers therefore need an understanding of the ethical parameters of their practice to navigate these complexities.